A Formulation of soothing gel ethanol extract of Red Shoot Leaves (Syzigium myrtifolium Walp) as an antioxidant - Lestari, Uce; Muhaimin, Muhaimin; Maimum, Maimum; Yuliana, Yuliana (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
Background: Natural antioxidant cosmetic products in the form of shooting gel from EEDPM (Syzigium myrtifolium Walp) with polyphenol and flavonoid content are able to fight free radicals and reduce oxidative damage to skin cells. Soothing gel works quickly absorbed, giving a fresh and comfortable effect on the skin without a sticky feeling. Method: The purpose of the study was to determine the comparison of the physical properties and stability of EEDPM and EEDPMM soothing gels and formulas that have very strong antioxidant activity potential. Comparison of evaluation physical properties and stability include organoleptic, homogeneity, pH, sedimentation rate, viscosity, adhesion and spreadability with concentrations of 1%, 2% and 3%. Antioxidant activity test with the DPPH method using a UV-Visible spectrophotometer. Results: The results of the analysis showed that the EEDPMMH and EEDPMM soothing gels have a light yellowish brown color with a rose odor, a semi-solid form with a thick and homogeneous consistency, pH 7.916 to 7.956; viscosity 20.173 cps to 20.370 cps; spreadability 3.966 to 4.766 cm with adhesion time > 1 second for the entire formula. The higher the concentration of EEDPMH and EEDPMM, the stronger the antioxidant activity. Conclusion: Typing It can be concluded that F3 Soothing Gel EDPMH and EDPMM are the best in terms of physical properties and stability and have a stronger IC50 than other formulas.